Wideband substrate‐integrated monopole antenna. Issue 8 (27th May 2016) - Lawrence, Nicholas P.; Fumeaux, Christophe; Abbott, Derek
ABSTRACT: A coaxial probe fed wideband low‐profile electric monopole cavity antenna with measured impedance bandwidth of 56% at a central operating frequency of 8 GHz is proposed. The antenna, based on a modified shorted square patch, effectively forms a substrate‐integrated cavity with four curved radiating slots at its periphery. The concave curvature of these four radiating slots provides a magnetic current loop mode while increasing bandwidth and reducing volume of the resonator. The proposed design may be easily fed using a 50 Ω probe feed and capacitive gap, and is robust to manufacturing tolerances, as parasitic modes are not excited. The design is compatible with applications requiring a vertically polarized signal with respect to the antenna surface. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1855–1857, 2016